Proprioceptive Training to Improve Static and Dynamic Balance in Elderly - Esposito, Giovanni; Altavilla, Gaetano; Di Domenico, Felice; Aliberti, Sara; D’Isanto, Tiziana; D’Elia, Francesca (International Journal of Statistics in Medical Research, 2021)
Background: The risk of falls is a major cause of disability in older adults. A single fall, for the elderly, increases the risk of frequent falls and often causes an increased fear of falling again, which can become debilitating. Objectives: The purpose of the present study was to test the effects of 12 weeks of proprioceptive training on the static and dynamic balance of older adults who have experienced at least one fall without compromising consequences. Method: The sample consisted of older adults, aged 60 to 80 years, randomly divided into two groups: an experimental group, which followed a proprioceptive training protocol at a physiotherapy studio, and a control group, which did not observe any treatment. Static and dynamic balance assessment was performed pre-and post-intervention. The tests administered were the Berg Balance Test for the evaluation of static balance, and the Four-Square Step Test, for dynamic balance. A questionnaire to assess confidence and fear of falling was administered at the end of the protocol. Independent sample t-test was performed to analyze differences between groups and two-way ANOVA to test the null hypothesis of no change different over time between groups (interaction intervention × time). A Chi-Square was performed to analyze perceptions. Conclusions: The results showed that 12 weeks of proprioceptive training effectively improved dynamic and static balance in older adults. The perceptions of the experimental group were more positive than the other one, in terms of the importance of physical activity to prevent the risk of falls, fear of falling again, and experience of falls during the last 12 weeks.